Business process changes on the implementation of artificial intelligence - Adorno, Oscar do Amaral (2020)
The process of digital transformation will affect all organizations. In businesses that have already started this process, artificial intelligence (AI) solutions have begun to appear. What are the current or incoming challenges and business process changes for Brazilian companies on this journey? Projects on digital transformation pose new challenges and cause organizational changes in business, operational and administrative processes. AI initiatives will have a competitive impact on organizations leading digital transformation. Our objective was to identify changes, potential effects, and impacts of AI technologies on business processes, transformation dynamics, organizational structures, and management. This qualitative research examined the cases of five large companies: four multinational subsidiaries based in Brazil and one Brazilian company. Their industries were telecom & technology, professional services, logistics services, chemistry, and financial services. These companies have been engaged in a long-term digital transformation and AI implementation. Different companies have distinct organizational structures for portfolio management and project implementation. Their challenges and changes were identified through content analysis with a semi-structured interview protocol. Publicly available data and data provided by the companies were collected. The main reported challenges were prioritization and selection of AI projects, lack of people with the required abilities, change management issues, cultural resistance, and integration with existing processes and systems. The most affected business processes were assistance services: external (customers) and internal relationships (employees) and process of internal activities (document analysis, health, and fiscal and supplier registration). Improving professional and academic work in this field has great relevance at this moment, as professionals and scholars have begun to understand the transformative potential of AI technologies in our society.